2015
DOI: 10.1097/mrr.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and efficacy of high-speed gait training with a voluntary driven exoskeleton robot for gait and balance dysfunction in patients with chronic stroke

Abstract: The aim of this pilot study was to investigate the feasibility of high-speed gait training with an exoskeleton robot hybrid assistive limb (HAL) in patients with chronic stroke, and to examine the efficacy of eight sessions (8 weeks) of gait training with a HAL compared with conventional physical therapy. Eighteen patients with chronic stroke were included in this study (nine each in the HAL and control groups). The HAL group underwent high-speed gait training with the HAL once a week for 8 weeks (20 min/sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 29 publications
5
54
0
1
Order By: Relevance
“…The results indicated that continuous gait training with HAL, in addition to conventional physical therapy, improved walking speed and balance function in a subject with chronic stroke, similar to the finding in our previous study15 ) that evaluated the effectiveness of HAL training for chronic stroke patients in comparison with control group. The improvements in gait and balance function in the present case were mostly maintained at least for two months after the gait training while the walking speed gradually tended to decrease slightly.…”
Section: Discussionsupporting
confidence: 86%
“…The results indicated that continuous gait training with HAL, in addition to conventional physical therapy, improved walking speed and balance function in a subject with chronic stroke, similar to the finding in our previous study15 ) that evaluated the effectiveness of HAL training for chronic stroke patients in comparison with control group. The improvements in gait and balance function in the present case were mostly maintained at least for two months after the gait training while the walking speed gradually tended to decrease slightly.…”
Section: Discussionsupporting
confidence: 86%
“…The study by Yoshimoto et al (30) showed significant improvement in the Timed Up and Go test in chronic stroke patients and in the functional reach test and the Berg Balance Scale after training in the HAL exoskeleton (once a week for 8 weeks, 20 min per session). The control group underwent conventional physical therapy for gait disturbances, but significant differences in balance were not observed (30). Also, the research of Hornby et al (13) or Hidler et al (31), comparing the effects of conventional rehabilitation with treatment on the Lokomat robot, did not show any significant differences in balance assessed by the Berg Balance Scale (13,31).…”
Section: Discussionmentioning
confidence: 91%
“…In the available literature, there are no studies which assess changes in balance among patients rehabilitated using an exoskeleton. Most authors have reported various aspects of gait (11,13,28,30), and only a few papers present some data about changes in the balance, but only based on subjective scales as the Berg Balance Scale (13,14). There are no studies in which changes in balance due to rehabilitation with the exoskeleton were examined using an objective tool such as a stabilometric platform.…”
Section: Discussionmentioning
confidence: 99%
“…At present, several studies have explored the use of HAL for gait training in different stages after stroke [77][78][79][80][81][82][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101]. The studies differ in terms of aim, design, duration of intervention, diagnosis, setting, and patient characteristics as well as allocation, randomization, blinding and outcome measures.…”
Section: Hal For Gait Training After Strokementioning
confidence: 99%